The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/febs.13382
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐induced conformation changes drive ATP hydrolysis and function in SMARCAL1

Abstract: Mutations and deletions in SMARCAL1, an SWI2/SNF2 protein, cause Schimke immuno-osseous dysplasia (SIOD). SMARCAL1 preferentially binds to DNA molecules possessing double-stranded to single-stranded transition regions and mediates annealing helicase activity. The protein is critical for alleviating replication stress and maintaining genome integrity. In this study, we have analysed the ATPase activity of three mutations -A468P, I548N and S579L -present in SIOD patients. These mutations are present in RecA-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…43 The S residue of the motif III in ADAAD is mutated in SIOD patients and has been studied in this context as discussed later in the review. 44 The motifs IV, V, and VI lie in the Rec A-like domain 2 and are important for the conformation of the protein.…”
Section: The Conserved Helicase Motifs Of Smarcal1mentioning
confidence: 99%
See 2 more Smart Citations
“…43 The S residue of the motif III in ADAAD is mutated in SIOD patients and has been studied in this context as discussed later in the review. 44 The motifs IV, V, and VI lie in the Rec A-like domain 2 and are important for the conformation of the protein.…”
Section: The Conserved Helicase Motifs Of Smarcal1mentioning
confidence: 99%
“…Mutation A468P that occurs on a residue present just one amino acid after motif I, mutation I548N that occurs on the residue present just before DESH box, and mutation S579L that occurs on the serine of motif III (SGTP) have been studied with respect to ATP hydrolysis and ligand binding. 44 All these three mutations result in impaired DNA binding in the presence of ATP such that the conformational change required for ATP hydrolysis does not occur leading to abrogated ATPase activity. 44 Motif VI associated mutation R870H results in altered conformation of the protein such that the mutant can no longer bind DNA either in the absence or presence of ATP with the same affinity as the wild-type protein.…”
Section: Siod and Smarcal1mentioning
confidence: 99%
See 1 more Smart Citation
“…We rationalized that if SMARCAL1 and BRG1 are necessary for DNA damage response pathway, then the patient-associated mutations should abrogate the DNA damage response. Therefore, the role of three SIOD-associated mutants-A468P, I548N, and S579L-was studied as previously it has been shown that these three mutants are unable to hydrolyze ATP due to impaired DNA binding [53]. In addition, three CSSassociated mutants-T895M, L921F, and M1011T-were also chosen as these three mutants mapped to the ATPase domain and are postulated to lack ATPase activity [27].…”
Section: Phosphorylation Of Atm and Atr Is Necessary For The Activatimentioning
confidence: 99%
“…It is possible that the Marcal1 K275M mutant protein may bind DNA less tightly than the wild-type protein. While ATP binding is not required for DNA binding by SMARCAL1, it can cause a conformational change that influences the DNA-binding constant (Gupta et al 2015). It is also possible that multiple Marcal1 molecules bind the nascent DNA and the presence of any wild-type protein is sufficient to rescue the Marcal1 K275M phenotype.…”
Section: Atp Binding Is Required For Marcal1 Activity During Sdsamentioning
confidence: 99%